PERAN ANGGOTA DPRD KABUPATEN INDRAGIRI HILIR DALAM MEMBANGUN PARTISIPASI MELALUI POLA PENYERAPAN ASPIRASI RAKYAT - jurnalmap map (MAP (Jurnal Manajemen dan Administrasi Publik), 2022)
The location of this research is DPRD Indragiri Hilir Regency, Riau. While the rationale for why the research location took the DPRD of Indragiri Hilir Regency, Riau as the research location, was the lack of research related to the title mentioned above which was carried out at the DPRD of Indragiri Hilir Regency, Riau, but also because of the spirit of the compilers themselves in an effort to contribute ideas for the institution to increasing its roles and functions, especially in capturing the aspirations of the people in the era of regional autonomy. The result of this research is that the pattern of absorption of community aspirations by the DPRD of Indragiri Hilir Regency is carried out in a formal and informal way. The formal method consists of recess and work visits, while the informal way is through informal visits, party activities, dialogue with NGOs and educational institutions, as well as through a cultural approach. Efforts to increase community participation in Indragiri Hilir Regency, especially related to the function of the DPRD itself, are to carry out several programs and activities that have been determined related to the function of the DPRD. The program includes: a program to improve the implementation of the budget function, a program to improve the implementation of the legislative function as well as a program to improve the supervisory function and empower community aspirations.